Nuclear safety in Southeast Asia : lessons from the nuclear pioneers - Julius Cesar I. Trajano (2015)
Southeast Asian states interested in acquiring nuclear energy may take lessons from the cumulative experience of 31 nuclear-powered states gained over the past 60 years. They need to study evolving international frameworks on safety regulation, human resources development and waste management.